Antimicrobial Activity of Propolis from the Brazilian Stingless Bees Melipona quadrifasciata anthidioides and Scaptotrigona depilis (Hymenoptera, Apidae, Meliponini) - Jaqueline Ferreira Campos; Thaliny Bonamigo; Paola dos Santos da Rocha; Vanessa Marina Branco Paula; Uilson Pereira dos Santos; José Benedito Perrella Balestieri; Denise Brentan Silva; Carlos Alexandre Carollo; Leticia M. Estevinho; Kely de Picoli Souza; Edson Lucas dos Santos (Microorganisms, 2022)
Melipona quadrifasciata anthidioides and Scaptotrigona depilis are species of stingless bees capable of producing propolis, which has considerable bioprospecting potential. In this context, the objective of this study was to determine the chemical compositions and evaluate the antimicrobial activity of propolis produced by M. q. anthidioides and S. depilis. The ethanolic extracts of propolis of M. q. anthidioides (EEP-M) and S. depilis (EEP-S) were prepared, and their chemical constituents were characterized by HPLC-ESI-MS. The antimicrobial activity was evaluated against bacteria and fungi, isolated from reference strains and hospital origin resistant to the action of antibiotics. From EEP-M, phenolic compounds were annotated, including gallic acid, ellagic acid, and flavonoids, as well as diterpenes and triterpenes. EEP-S showed mainly triterpene in its chemical composition. Both extracts inhibited the growth of medically relevant bacteria and fungi, including hospital-acquired and antimicrobial-resistant. In general, EEP-S showed better antimicrobial activity compared to EEP-M. The MIC of EEP-S against vancomycin-resistant Enterococcus faecalis was 3.50 mg/mL, while the MIC of EEP-M was 5.33 ± 0.16 mg/mL. In conclusion, this study shows that propolis produced by M. q. anthidioides and S. depilis has the potential to be used for the prevention or treatment of microbial infections.